Association Between Serum Methylmalonic Acid (A Marker of Mitochondrial Dysfunction) and Serum Neurofilament Light Chains in a U.S. Population: a Cross‐Sectional Analysis From NHANES 2013–2014 - Jun Wei; Yang Liu; Ya Li (Brain and Behavior)
Abstract Introduction Serum neurofilament light chain (sNfL) is an emerging biomarker of neuronal damage in various neurological disorders. Methylmalonic acid (MMA) serves as a biomarker for mitochondrial dysfunction. This study aimed to investigate the relationship between MMA and sNfL. Methods Data were obtained from the 2013–2014 National Health and Nutrition Examination Survey (NHANES). Multiple linear regression modeling was employed to confirm the association between MMA and sNfL, while smooth curve fitting was utilized to explore the potential nonlinear relationship. Subgroup analyses and interaction tests were conducted to assess the stability of the association across different subgroups. Results This study included 2,070 participants with a mean age of 46.89 ± 15.36 years. In the fully adjusted model, each 1 nmol/L increase in serum MMA was associated with a 3.11 pg/mL increase in sNfL (95% CI: 0.91 to 5.31; p = 0.0056). Participants in the highest quartile of MMA had significantly higher sNfL levels compared to those in the lowest quartile (β = 5.09; 95% CI: 2.30 to 7.87; p = 0.0004). A nonlinear relationship was observed, with an inflection point at 5.51 nmol/L of MMA, while above the threshold, MMA was strongly associated with higher sNfL levels (β = 12.57, 95% CI: 7.14 to 17.99; p < 0.0001). Subgroup analyses further suggested stronger associations among individuals with diabetes or low vitamin B12 status (P for interaction < 0.05). Conclusions Our study found a significant positive association between serum MMA and sNfL. Further prospective studies are warranted.